A theoretical understanding of the literature on student voice in the science classroom. Issue 1 (2nd January 2018) - Laux, Katie
Abstract: Background : Incorporating student voice into the science classroom has the potential to positively impact science teaching and learning. However, students are rarely consulted on school and classroom matters. This literature review examines the effects of including student voice in the science classroom. Purpose : The purpose of this literature review was to explore the research on student voice in the science classroom. This review includes research from a variety of science education sources and was gathered and analyzed using a systematic literature review process. Design and methods : I examined articles from a variety of educational journals. I used three key terms as my primary search terms: student voice, student perceptions, and student perspectives . The primary search terms were used in conjunction with qualifiers that included science education, science curriculum, student emergent curriculum, student centered curriculum, and science . In order to be included in the literature review, articles needed to be published in peer-reviewed, academic journals, contain clearly defined methods (including quantitative, qualitative, or mixed methods), include research conducted in K through 12 classrooms, include the term 'student voice', and focus specifically on science. I included articles from a variety of science classrooms including general middle school science, science-specific after-school programs, secondary science classrooms in a variety of countries, and physics, biology, and aerospace classrooms. No restrictions were placed on the country in which the research was conducted or on the date of the research. Conclusions : The results of the literature review process uncovered several themes within the literature on student voice. Student voice research is situated within two main theoretical perspectives, critical theory and social constructivism, which I used as the main themes to structure my findings. I also identified subcategories under each main theme to further structure the results. Under critical theory, I identified three subcategories: determining classroom topics, developing science agency, and forming identities. Under social constructivism, I discovered four subcategories: forming identities, incorporating prior knowledge and experience, communicating interest in topics and classroom activities, and improving student–teacher relationship. The research supports that allowing students a voice in the classroom can lead them to feel empowered, able to construct their own meaning and value in science, demonstrate increased engagement and achievement, and become more motivated. I conclude students should be allowed a voice in the science classroom and to continue to ignore these voices would be a disservice to students and educators alike.